THE IMPORTANCE OF ORGANIZING CHILDREN’S ACTIVITIES IN PREPARATION FOR SCHOOLING - Karimova Shoira Bakhtiyarovna (Galaxy International Interdisciplinary Research Journal, 2024)
The prerequisites for successful schooling are the preparation of preschoolers for this. Readiness for learning is the formation of all mental processes, as well as the personality of a preschooler as a whole, at the level that is necessary for successful adaptation and learning in elementary school. Despite the differences in approaches to learning, the parameters for which in currently assessing the readiness of the child for school.